(untitled) (Bulletin KNOB, 1991)
The modern protection of monuments must be disposed of conservative views with regard to urban renewal. This article deals with monuments as spearheads in a future-directed policy. Hereby a strategy which integrates the protection of monuments with other fields such as town development and urban renewal replaces the interest in each separate volume or in the urban ensemble. The author sketches three perspectives: reorganization of the civil service occupied with the administration and preservation of a confined number of registered monuments. Second: knowledge of the town’s spatial development must be acquired systematically which knowledge can promote the integration of historical potencies and qualities with the contemporary town plan. Thirdly: a completely automated data-base with regard to the town’s development can democratize this knowledge to the citizenry. Functional spread of the results of advanced historical research is a condition to revive a specific cultural identity of the town. The new Act of Monuments (1988) provides municipalities with a better position with respect to the protection of monuments. A mainly technical office modestly manned and for preference integrated with the department of Area Planning must use new juridical and financial possibilities to give the protection of monuments a pioneer-function in the process of the improvement of urban space. Some qualifications of the municipal committee of monuments can be handed over to the board of welfare monuments being submitted to the same rules as other building schemes. For monuments are no exception to the rule, monuments are leading. Thus Giorgio Grassi’s design for the Public Library in Groningen makes up a wonderful connection with history raising the artificial boundary line between monument and contemporary architecture. The office of monuments in the same town must be manned with an archaeologist, a historian of structural engineering and a historian of architecture, the knowledge as acquired by these specialists on the one side concerning stock-taking and preservation of valuable artifacts, on the other hand the gradual design of a history of the material beauty of the town. This design contributes to a historical cultural notion and offers starting points for the contemporary design of the town as well. Data with respect to the history, preservation and restoration of the registered monuments can be coordinated by means of a computerized information system, which strengthens the coherence of the municipal policy of monuments and the process of urban renewal. By the coupling of three-dimensional representation with relevant texts and sources this system offers possibilities to the scientific results of research and the presentation of data on the town’s history to the citizenry. At the development of this system one has to take such future use into consideration.